2015
DOI: 10.1093/brain/awv169
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic functional connectivity differentiates minimally conscious from unresponsive patients

Abstract: Despite advances in resting state functional magnetic resonance imaging investigations, clinicians remain with the challenge of how to implement this paradigm on an individualized basis. Here, we assessed the clinical relevance of resting state functional magnetic resonance imaging acquisitions in patients with disorders of consciousness by means of a systems-level approach. Three clinical centres collected data from 73 patients in minimally conscious state, vegetative state/unresponsive wakefulness syndrome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
269
6
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 317 publications
(324 citation statements)
references
References 86 publications
33
269
6
3
Order By: Relevance
“…To help address the diagnostic and prognostic challenge in disorders of consciousness, a range of neuroimaging technologies have been proposed for assessing ongoing brain activity with sophisticated analytical techniques. These include MRI (Demertzi et al, 2015), PET (Thibaut et al, 2012;Stender et al, 2014) and high density EEG (Lehembre et al, 2012;King et al, 2013;Lechinger et al, 2013;Chennu et al, 2014;Sitt et al, 2014). EEG in particular is an attractive option in this context as it is portable, cost-effective, and relatively feasible to deploy at the patient's bedside.…”
Section: Introductionmentioning
confidence: 99%
“…To help address the diagnostic and prognostic challenge in disorders of consciousness, a range of neuroimaging technologies have been proposed for assessing ongoing brain activity with sophisticated analytical techniques. These include MRI (Demertzi et al, 2015), PET (Thibaut et al, 2012;Stender et al, 2014) and high density EEG (Lehembre et al, 2012;King et al, 2013;Lechinger et al, 2013;Chennu et al, 2014;Sitt et al, 2014). EEG in particular is an attractive option in this context as it is portable, cost-effective, and relatively feasible to deploy at the patient's bedside.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic studies have demonstrated a difference in cortical auditory processing between vegetative state (VS) patients that lack the ability to interact with their environment and minimally conscious patients, who demonstrate behavioral interactions 5, 6, 7, 8. Attempts to discriminate auditory attention and processing in these MCS patients with electroencephalography (EEG) have focused on event‐related potential paradigms utilizing single words and repeated sound sequences 9, 10, 11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Plusieurs études ont notamment montré que la connectivité fonctionnelle du réseau du mode par défaut diminue plus le niveau de conscience est bas (conscient > ECM > EV/ENR > coma) [38,44,45].…”
Section: Irm Fonctionnelleunclassified